2018
DOI: 10.1038/s41421-018-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell specific inhibition of Wnt/β-catenin signaling by forced intracellular acidification

Abstract: Use of the diabetes type II drug Metformin is associated with a moderately lowered risk of cancer incidence in numerous tumor entities. Studying the molecular changes associated with the tumor-suppressive action of Metformin we found that the oncogene SOX4, which is upregulated in solid tumors and associated with poor prognosis, was induced by Wnt/β-catenin signaling and blocked by Metformin. Wnt signaling inhibition by Metformin was surprisingly specific for cancer cells. Unraveling the underlying specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 85 publications
4
25
0
Order By: Relevance
“…This finding is consistent with the upregulation of the DNA damage-inducible transcript 3 (DDIT3), a key gene in the upregulated pathway, which encodes a stress-inducible transcription factor that induces cell cycle arrest and apoptosis in mammalian cells. Our finding is consistent with a previous study that showed that monensin induced DDIT3, a key inhibitor of the Wnt signalling pathway [42], in prostate cancer cells [43]. The key genes identified in those downregulated pathways are CCNA2, that controls both the G1/S and the G2/M transition phases of the cell cycle, and MYBL2, that functions as a physiological regulator of cell cycle progression.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the upregulation of the DNA damage-inducible transcript 3 (DDIT3), a key gene in the upregulated pathway, which encodes a stress-inducible transcription factor that induces cell cycle arrest and apoptosis in mammalian cells. Our finding is consistent with a previous study that showed that monensin induced DDIT3, a key inhibitor of the Wnt signalling pathway [42], in prostate cancer cells [43]. The key genes identified in those downregulated pathways are CCNA2, that controls both the G1/S and the G2/M transition phases of the cell cycle, and MYBL2, that functions as a physiological regulator of cell cycle progression.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is also consistent with posterior PSM and tail bud cells exhibiting Warburg-like metabolism with high aerobic glycolysis and an inverted pHe/pHi gradient as compared to more differentiated cells. Decreasing the pHi in Wnt-addicted tumor cells was recently shown to inhibit Wnt signaling, as reported here for differentiating tail bud cells (26). Thus our findings further emphasize the tight similarity between the developing tail bud cell and cancer cells that exhibit high Warburg metabolism resulting in high pHi and low pHe (27), supporting the notion that some tumor cells might reactivate a developmental metabolic program.…”
Section: Main Textsupporting
confidence: 87%
“…Boosting glycolysis with mitochondria inhibitors such as Metformin (MET) have also been proposed to be a method to decrease pHi in various cancer cell lines, BC among them [96], alone and/or in combination with the MCT inhibitor Simvastatin [97] ( Table 2).…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%
“…MET has been proposed to be a viable anticancer drug since it induces intracellular hyperacidification in tumor xenograft models through inhibition of Wnt signaling, a feature found to be selective for cancer cells [96]. During the last few years MET has been introduced as an anticancer agent in clinical oncology after it was reported to decrease mortality of BC patients [236,237,[246][247][248], increasing the survival of triple-negative BC patients [248] .…”
Section: ) Hydrogen Ion Dynamics In Multiple Drug Resistance (Mdr) Imentioning
confidence: 99%